sinx-cosx-tanx=-1

Simple and best practice solution for sinx-cosx-tanx=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for sinx-cosx-tanx=-1 equation:

Simplifying
sinx + -1cosx + -1tanx = -1
Reorder the terms:
-1antx + -1cosx + insx = -1
Solving
-1antx + -1cosx + insx = -1
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add 'cosx' to each side of the equation.
-1antx + -1cosx + cosx + insx = -1 + cosx
Combine like terms: -1cosx + cosx = 0
-1antx + 0 + insx = -1 + cosx
-1antx + insx = -1 + cosx
Add '-1insx' to each side of the equation.
-1antx + insx + -1insx = -1 + cosx + -1insx
Combine like terms: insx + -1insx = 0
-1antx + 0 = -1 + cosx + -1insx
-1antx = -1 + cosx + -1insx
Divide each side by '-1ntx'.
a = n-1t-1x-1 + -1cn-1ost-1 + ist-1
Simplifying
a = n-1t-1x-1 + -1cn-1ost-1 + ist-1
Reorder the terms:
a = -1cn-1ost-1 + ist-1 + n-1t-1x-1`